Potential of Aluminum Drug Packages with Press-Through Packaging Considering Usability for a Wide Range of Users - Kubota K; Shimada M; Ura H; Sadamoto K (Medical Devices: Evidence and Research)
Kiyoshi Kubota,1– 3,* Morio Shimada,3,* Hiroyuki Ura,1,* Kiyomi Sadamoto1,2,4,* 1Department of Clinical Pharmacy, Shonan University of Medical Science, Yokohama, Japan; 2MECSION, General Incorporated Association, Hiratsuka, Japan; 3Department of Radiological Sciences, Faculty of Health Sciences, Komazawa University, Tokyo, Japan; 4Sadamoto Clinic, Kanagawa, Japan*These authors contributed equally to this workCorrespondence: Kiyoshi Kubota, Email kubota.kiyoshi8@gmail.comPurpose: Press-through packages (PTPs) are frequently used for the packaging of prescription drugs in Japan. However, tablets or capsules packaged in PTPs may become unstable and difficult to store. Therefore, aluminum pouches (pillow packages) are applied as an additional packaging option. Especially for 10-sheet tablet (capsule) PTPs, there are many opportunities for health-care professionals (mainly pharmacists) to open pillow packages during the dispensing process. However, aluminum pouches (pillow packages) that are easy to open and store appropriately by not only pharmacists, but also patients, are needed.Methods: A 100-unit PTP (pillow package) with conventional specifications ① and two other products (②: open vertically by a wavy processed half-cut and ③: pinch the backlining open) were developed with the aim of improving the ease of opening. The study participants, consisting of pharmacists and patients, performed tasks such as opening and taking drugs out of the PTP for each sample, and evaluated the differences in usability.Results: The results of a sensory test revealed that pharmacists rated products ② and ③ higher than product ①. On the other hand, patients, including those with weak grip and pinching strengths, rated ③ highly, confirming the superiority of usability in the order of ③, ②, and ①. In addition, item ③ was successfully opened by all patients.Conclusion: The present results indicated the superiority of the developed pillow packaging, which enables pharmacists to save time in the dispensing process. In addition, product ③ was evaluated highly by patients, especially those with disabilities, for its ease of use not only in terms of opening, but also storage. Sensory testing by actual users applying ergonomic methods enabled a multifaceted evaluation of the products and provided insights into the actual status of pharmacists’ dispensing work (product issues) and patients’ daily medication use.Keywords: pharmacists, patients, improved openability, sarcopenia, rheumatoid arthritis